Clinical Practice Guidelines in Traditional Chinese Medicine Rehabilitation—Rheumatoid Arthritis - Working Group on Setting up Standardization Guidelines of Rheumatoid Arthritis in Traditional Chinese Medicine Rehabilitation; Jie LUO; Peimin LAN; Hanyu CHEN; Xinggang FANG; Zengfeng CHEN; Yuming NIU; Chao ZHANG; Feng GAO; Guohong WEN; Junhua WANG; Su ZHENG; et al. (康复学报)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by erosive arthritis, eventually leading to joint deformity and loss of function. To standardize the operating standards of RA for traditional Chinese medicine (TCM) and better guide clinical practice, the experts group compiled RA clinical practice guidelines for TCM rehabilitation according to the rules of clinical practice guidelines based on the principles of evidence-based medicine combined with expert consensus and argumentation, and clinical evaluation. Aiming to provide more specialized medical guidance for clinical practitioners, such as rheumatology of TCM, rheumatology of integrated traditional Chinese and Western medicine, TCM rehabilitation, and rheumatology, the diagnosis and treatment process of RA, including scope, normative references, terminology and definitions, diagnostic criteria, assessment criteria, treatment, and other aspects, were systematized and standardized in the guidelines. The part of treatment is divided into rehabilitation treatment, TCM treatment, psychological rehabilitation, diet, and surgical treatment. Rehabilitation therapy includes physical factor therapy, exercise therapy, operation therapy, orthopedic apparatus, and intra-articular injection; and the TCM treatment includes the acupuncture and moxibustion, the massage, the TCM practice and the TCM syndrome differentiation. The guidelines has excellent practicality, scientificity and effectiveness, and it will provide a standardized diagnosis and treatment process for RA's TCM rehabilitation treatment, and provide reliable evidence for better clinical decision-making practice.